Unanswered questions and unquestioned answers: the challenges of crop residue retention and weed control in Conservation Agriculture systems of southern Africa - Thierfelder, Christian; Mhlanga, Blessing; Ngoma, Hambulo; Marenya, Paswel; Md Abdul Matin; Tufa, Adane H.; Alene, Arega D.; Chikoye, David (Cambridge University Press, 2024)
Production and utilization of crop residues as mulch and effective weed management are two central elements in the successful implementation of Conservation Agriculture (CA) systems in southern Africa. Yet, the challenges of crop residue availability for mulch or the difficulties in managing weed proliferation in CA systems are bigger than a micro-level focus on weeds and crop residues themselves. The bottlenecks are symptoms of broader systemic complications that cannot be resolved without appreciating the interactions between the current scientific understanding of CA and its application in smallholder systems, private incentives, social norms, institutions, and government policy. In this paper, we elucidate a series of areas that represent some unquestioned answers about chemical weed control and unanswered questions about how to maintain groundcover demanding more research along the natural and social sciences continuum. In some communities, traditional rules that allow free-range grazing of livestock after harvesting present a barrier in surface crop residue management. On the other hand, many of the communities either burn, remove, or incorporate the residues into the soil thus hindering the near-permanent soil cover required in CA systems. The lack of soil cover also means that weed management through soil mulch is unachievable. Herbicides are often a successful stopgap solution to weed control, but they are costly, and most farmers do not use them as recommended, which reduces efficacy. Besides, the use of herbicides can cause environmental hazards and may affect human health. Here, we suggest further assessment of the manipulation of crop competition, the use of vigorously growing cover crops, exploration of allelopathy, and use of microorganisms in managing weeds and reducing seed production to deplete the soil weed seed bank. We also suggest in situ production of plant biomass, use of unpalatable species for mulch generation and change of grazing by-laws towards a holistic management of pastures to reduce the competition for crop residues. However, these depend on the socio-economic status dynamics at farmer and community level.